Analysis of Designing Green Architecture Based on Building Information Modeling (BIM) Technology. Issue 1 (July 2021) - Long, Rui; Li, Yanling
Abstract: Architecture industry is one of the most important energy consumers and environmental polluters. Ensuring the ecological stability and the environmental sustainability for humankind, developing green architecture is an urgent need. How to design green architecture properly is the key to constructing energy-saving and sustainable architecture. This paper analyzed the designing procedures of green architecture and the problems in the designing process, and explained how to use Building Information Modeling (BIM) technology to deal with the problems, providing references for designing green architecture.